The transfer of a laboratory based hypothesis to a clinically useful therapy: the development of anti-TNF therapy of rheumatoid arthritis. - Feldmann, M; Brennan, F; Williams, R; Woody, J; Maini, R (2004)
The development of anti-TNF therapy is a key step forward in rheumatology as it is the first new therapy for based on investigating the molecular mechanisms of this disease. This chapter reviews how this discovery was made.